Black zirconia composite sintered body and method for producing same
By adding ZrO2, HfO2 and Nb2O5/Ta2O5 to the zirconia composite sintered body and using end capping elements or ions, the problem of poor machining properties of zirconia sintered bodies is solved, and the mechanical machining and appearance design is improved, ensuring that Productivity and economy.
Patent Information
- Application Number
- CN202380044116.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-01
- Filing Date
- 2023-06-01
- Publication Date
- 2025-01-10
AI Technical Summary
The existing zirconia sintered bodies have poor machining properties in the sintered state, making it difficult to achieve mechanical processing. The high content of zirconia leads to reduced machining, changes in color, fast consumption of processing tools, and low productivity and economicality.
By adding ZrO2 and HfO2 as phase change stabilizers to the zirconia composite sintered body, including Nb2O5 and/or Ta2O5, combined with capping elements or ions, the microstructure and grain boundary strength of the sintered body are optimized to improve machining and Designability.
A black zirconia composite sintered body with excellent mechanical processing properties, short processing time, low tool consumption, multiple continuous processing units, and excellent strength and appearance design properties in the sintered body state.
Smart Images

Figure BDA0005161825670000321 
Figure BDA0005161825670000331 
Figure HDA0005161825720000011
Abstract
Description
Technical Field
[0001] The present invention relates to a black zirconia composite sintered body and a method for producing the same. More specifically, the present invention relates to a black zirconia composite sintered body having excellent strength and excellent workability in a sintered body state and a method for producing the same. Background Art
[0002] Due to the innovation of communication technology such as 5G, radio waves used for communication are moving to high-frequency bands. The back panels of 5G-compatible smartphones are mainly made of metal, but metal is not suitable for the transceiver of high-frequency radio waves, so plastic, glass, and ceramics are used.
[0003] Among them, black ceramics are sometimes used because black gives a high-class feel and has high design properties.
[0004] In addition, there is a demand for zirconium oxide as a ceramic with high design. However, zirconium oxide is a difficult-to-process material in the state of a sintered body. Therefore, if a sintered zirconium oxide is used as a part of a smartphone material, the processing cost becomes high due to the difficult-to-process nature of the sintered body.
[0005] Under such circumstances, since black is essential as the color of the housing of a smartphone, black-based free-machining ceramics have been developed by containing zirconium oxide but not as a main component (for example, Patent Document 1).
[0006] On the other hand, black zirconia sintered bodies have been developed from the viewpoint of excellent design properties, although their workability is significantly inferior (for example, Patent Documents 2 and 3).
[0007] In addition, regarding zirconia sintered bodies, although not black and for the dental field, machinable zirconia sintered bodies with improved machinability have also been developed (for example, Patent Document 4). For example, Patent Document 4 discloses a machinable zirconia and a method for manufacturing the same, wherein the machinable zirconia sintered body is a sintered body formed by including a tetragonal zirconia composite powder and a TiO2 nanopowder having a mass ratio of greater than 0 mass % and less than 2.5 mass % relative to the aforementioned zirconia composite powder, wherein the tetragonal zirconia composite powder contains 79.8 to 92 mol % of ZrO2 and 4.5 to 10.2 mol % of Y2O3, and 3.5 to 7.5 mol % of Nb2O5 or 5.5 to 10.0 mol % of Ta2O5.
[0008] Prior art literature
[0009] Patent Literature
[0010] Patent Document 1: Japanese Patent Application Publication No. 2001-354480
[0011] Patent Document 2: Japanese Patent Application Publication No. 2006-342036
[0012] Patent Document 3: Japanese Patent Application Publication No. 2017-77976
[0013] Patent Document 4: Japanese Patent Application Publication No. 2015-127294 Summary of the invention
[0014] Problems to be solved by the invention
[0015] Zirconium oxide is used as a black pigment obtained by reduction firing in Patent Document 1. However, if the content of zirconium oxide increases, the machinability decreases, so the blending ratio of zirconium oxide is low.
[0016] Patent Document 2 proposes a zirconia sintered body having a deep black color. Patent Document 3 also proposes a black zirconia sintered body that addresses the problem of a change in color tone due to sintering when obtaining the zirconia sintered body.
[0017] However, both Patent Documents 2 and 3 fail to solve the problem of poor processability.
[0018] In addition, the zirconia sintered body disclosed in Patent Document 4 can be machined even in the sintered state. However, it is difficult to say that the processability is excellent, the processing time for cutting out the processed body is long, and there is still room for improvement in processability. It is not black, and has excellent light transmittance, so the color tone is completely different.
[0019] Furthermore, although the zirconia sintered body disclosed in Patent Document 4 can be machined, the number of processed bodies obtained by continuous processing using one processing tool is small and the processing tool is consumed quickly. Therefore, there are problems such as increased frequency of replacing the processing tool, increased tool replacement time, and reduced productivity and economy.
[0020] As described above, Patent Document 4 also only stops at the level of being able to process zirconia sintered bodies, and there is a unique problem caused by the sintering state of zirconia, such as the processing of zirconia sintered bodies is very difficult. Therefore, it is still difficult to provide a zirconia sintered body with excellent processability in the sintered body state, and a zirconia sintered body with excellent processability in the sintered body state and black color has not been obtained.
[0021] An object of the present invention is to provide a zirconia composite sintered body which has excellent machinability in a sintered body state and is black.
[0022] Solutions to Solve Problems
[0023] The present inventors have repeatedly conducted research efforts to solve the above-mentioned problems, and as a result, found that the problem can be solved by further including capping elements or ions in a black zirconia composite sintered body containing ZrO2, HfO2, a stabilizer capable of inhibiting the phase transformation of zirconia, and Nb2O5 and / or Ta2O5 in a specified proportion. Based on this insight, further research was conducted to complete the present invention.
[0024] That is, the present invention includes the following inventions.
[0025] [1] A black zirconia composite sintered body comprising ZrO2, HfO2, a stabilizer capable of suppressing phase transformation of zirconia, and Nb2O5 and / or Ta2O5,
[0026] In the total of 100 mol% of ZrO2, HfO2, the above stabilizer, Nb2O5 and Ta2O5,
[0027] The total content of ZrO2 and HfO2 is 78-97.5 mol%.
[0028] The content of the stabilizer is 1 to 12 mol%.
[0029] The total content of Nb2O5 and Ta2O5 is 1 to 9 mol%.
[0030] The black zirconia composite sintered body further includes elements or ions derived from a capping agent.
[0031] [2] The black zirconia composite sintered body according to [1], wherein the content of the element or ion derived from the capping agent is greater than 0 mol% and less than 5.0 mol% relative to the total of 100 mol% of ZrO2, HfO2, the stabilizer, Nb2O5 and Ta2O5.
[0032] [3] The black zirconia composite sintered body according to [1] or [2], wherein a sample having a diameter of 15 mm and a thickness of 1.2 mm is used, and the chroma C* calculated from a* and b* measured against a white background of the L*a*b* colorimetric system is 10 or less.
[0033] [4] The black zirconia composite sintered body according to [1] or [2], wherein the colorimetric value obtained by using a sample having a diameter of 15 mm and a thickness of 1.2 mm on a white background of the L*a*b* colorimetric system is L*≤60, |a*|≤3 and |b*|≤3.
[0034] [5] A black zirconia composite sintered body according to any one of [1] to [4], wherein the element or ion derived from the capping agent includes at least one element or ion selected from Cu, Ag, Li, Na, K, Rb, Cs, Fr, At, I, Br, Cl and F.
[0035] [6] A black zirconia composite sintered body according to any one of [1] to [5], wherein when the content of the aforementioned stabilizer is set to A mol % and the total content of Nb2O5 and Ta2O5 is set to B mol %, A / B is greater than or equal to 0.9 and less than or equal to 3.
[0036] [7] The black zirconia composite sintered body according to any one of [1] to [6], wherein the stabilizer contains Y2O3 and / or CeO2.
[0037] [8] A black zirconia composite sintered body according to any one of [1] to [7], which further comprises a zirconia reinforcing agent, wherein the content of the zirconia reinforcing agent is greater than 0 mass % and less than 5.0 mass % relative to the total of 100 mass % of ZrO2, HfO2, the aforementioned stabilizer, Nb2O5 and Ta2O5.
[0038] [9] The black zirconia composite sintered body according to [8], wherein the zirconia reinforcing agent comprises TiO2 and / or Al2O3.
[0039]
[10] The black zirconia composite sintered body according to [9], wherein the zirconia reinforcing agent contains TiO2, and the content of TiO2 is 0.6 to 3.7% by mass.
[0040]
[11] The method for producing a black zirconia composite sintered body according to any one of [1] to
[10] , comprising:
[0041] A step of producing a formed body using a raw material composition, wherein the raw material composition comprises ZrO2, HfO2, a stabilizer capable of suppressing phase transformation of zirconium oxide, and Nb2O5 and / or Ta2O5,
[0042] In the total of 100 mol % of ZrO2, HfO2, the above-mentioned stabilizer, Nb2O5 and Ta2O5, the total content of ZrO2 and HfO2 is 78 to 97.5 mol %,
[0043] The content of the stabilizer is 1 to 12 mol%.
[0044] The total content of Nb2O5 and Ta2O5 is 1 to 9 mol%.
[0045] The raw material composition further comprises a capping agent; and
[0046] A step of sintering the molded body.
[0047]
[12] The method for producing a black zirconia composite sintered body according to
[11] , wherein the step of sintering the molded body includes a step of performing reduction sintering.
[0048]
[13] The method for producing a black zirconia composite sintered body according to
[11] or
[12] , wherein the terminal capping agent contained in the raw material composition is a compound that can form a monovalent ion,
[0049] The method for producing a zirconium oxide composite sintered body further includes a step of wet-mixing the respective raw materials of the raw material composition in a solvent containing water to obtain the raw material composition.
[0050]
[14] The method for producing a black zirconia composite sintered body according to any one of
[11] to
[13] , wherein in the raw material composition, the stabilizer includes a stabilizer that is insoluble in ZrO2 and HfO2.
[0051] Effects of the Invention
[0052] According to the present invention, it is possible to provide a zirconium oxide composite sintered body which has excellent machinability in a sintered state and is black.
[0053] In addition, according to the present invention, a black zirconia composite sintered body can be provided, which can be machined in the state of a sintered body, and the machining time is short based on the machining, and the consumption of machining tools can be suppressed. By continuous machining using one machining tool (hereinafter also referred to as "continuous machining"), a large number of machined bodies can be cut out, and the productivity and economy are excellent.
[0054] Furthermore, according to the present invention, a black zirconia composite sintered body having excellent strength and excellent design properties can be provided.
[0055] Furthermore, according to the present invention, pressure sintering in the method for producing a black zirconia composite sintered body is unnecessary.
[0056] Brief description of the attached figure
[0057] Figure 1 It is a schematic diagram showing the estimated structure of the black zirconia composite sintered body of the present invention.
[0058] Figure 2 This is a schematic diagram showing the presumed mechanism of action involving the element or ion derived from the capping agent of the present invention. DETAILED DESCRIPTION
[0059] The black zirconia composite sintered body of the present invention comprises ZrO2, HfO2, a stabilizer capable of suppressing the phase transformation of zirconia (hereinafter also referred to as "stabilizer"), and Nb2O5 and / or Ta2O5.
[0060] In the total of 100 mol % of ZrO2, HfO2, the above-mentioned stabilizer, Nb2O5 and Ta2O5, the total content of ZrO2 and HfO2 is 78 to 97.5 mol %,
[0061] The content of the stabilizer is 1 to 12 mol%.
[0062] The total content of Nb2O5 and Ta2O5 is 1 to 9 mol%.
[0063] The black zirconia composite sintered body further includes elements or ions derived from a capping agent.
[0064] The black zirconia composite sintered body of the present invention refers to a state (sintered state) in which ZrO2 particles (powder) are completely sintered. It should be noted that in this specification, the upper limit and lower limit of the numerical range (the content of each component, the ratio calculated from each component, the value and each physical property, etc.) can be appropriately combined.
[0065] In this specification, machining includes cutting and grinding.
[0066] In addition, the machining may be either wet machining or dry machining, and is not particularly limited.
[0067] In the present specification, elements or ions derived from capping agents (hereinafter also referred to as "capping elements or ions") refer to elements or ions that cap the ends of the bonding sites (bonding hands) of the zirconium oxide-based composite oxides in the black zirconium oxide composite sintered body composed of zirconium oxide-based composite oxides, thereby weakening the strength of the crystal interface (hereinafter also referred to as "grain boundary") (hereinafter also referred to as "grain boundary strength").
[0068] The capping agent can cap a portion of the crystal grain boundaries.
[0069] The term "capping" means that the target element or ion (capping element or ion) is bonded to the bonding site of the zirconium oxide-based composite oxide instead of the metal element and exists at the crystal grain boundary.
[0070] It is presumed that the capping elements or ions exist at the grain boundaries in the form of +1-valent cations or -1-valent anions, and the capped cations or anions are electrostatically repelled from each other, thereby weakening the grain boundary strength.
[0071] In the present specification, the content of each component in the black zirconia composite sintered body can be calculated from the amount of raw materials charged.
[0072] In addition, the content of each component of ZrO2, HfO2, stabilizer, Nb2O5 and Ta2O5 in the black zirconia composite sintered body can also be measured by, for example, inductively coupled plasma (ICP) emission spectrometry, fluorescent X-ray analysis, etc.
[0073] The content rate (mol %) of the element or ion derived from the capping agent is the external addition rate relative to the total of 100 mol % of ZrO2, HfO2, the aforementioned stabilizer, Nb2O5 and Ta2O5. Therefore, the content rate of the element or ion derived from the capping agent in the black zirconia composite sintered body can be calculated by converting the added amount (mass) of the raw materials at the time of addition into mol %.
[0074] In addition, the content rate (mass %) of the zirconia reinforcing agent is the external addition rate relative to the total of 100 mass % of ZrO2, HfO2, the above-mentioned stabilizer, Nb2O5 and Ta2O5. Therefore, the content rate of the zirconia reinforcing agent in the black zirconia composite sintered body can be calculated from the added amount (mass) of the raw materials when added.
[0075] The reason why the black zirconia composite sintered body of the present invention has suitable strength and high machinability and can be machined in a sintered state is not yet clear, but is presumed as follows.
[0076] It can be speculated that in the black zirconia composite sintered body containing ZrO2, HfO2, a stabilizer capable of inhibiting the phase transformation of zirconia, and Nb2O5 and / or Ta2O5, due to the presence of capping elements or ions at the crystal grain boundaries, the capping elements or ions reduce the grain boundary strength in the form of +1-valent cations or -1-valent anions, act in the direction of facilitating the peeling of particles, making it easier to cut and improving machinability.
[0077] It can be inferred that the black zirconia composite sintered body of the present invention has the following structure, which includes: zirconia particles 1 containing ZrO2, HfO2, a stabilizer capable of inhibiting the phase transformation of zirconia, and Nb2O5 and / or Ta2O5, a stripping component 2 containing a capping element or ion, and further, as needed, an adhesive component 3 containing ZrO2, HfO2, Nb2O5 and / or Ta2O5, and a metal element (such as Ti, etc.) derived from the zirconia strengthener.
[0078] Part of each of ZrO 2 , HfO 2 , and Nb 2 O 5 and / or Ta 2 O 5 exists in both the zirconium oxide particles 1 and the adhesive component 3 .
[0079] Furthermore, it can be inferred that in the zirconia composite sintered body of the present invention, there are grain boundaries 4 where no exfoliation component 2 exists, and exfoliation components 2 containing capping elements or ions exist appropriately at the grain boundaries, so that the grain boundary strength can be appropriately reduced while keeping the strength reduction to a minimum.
[0080] Figure 1 A schematic diagram showing an estimated structure of a zirconia composite sintered body according to an embodiment including a zirconia reinforcing agent. Even in the presence of an adhesive component 3 in a zirconia composite sintered body including a zirconia reinforcing agent, the effect of reducing the grain boundary strength obtained by the exfoliation component 2 is not suppressed, and the strength can be improved.
[0081] The capping element or ion forms a +1-valent cation or -1-valent anion at the grain boundary of the black zirconia composite sintered body, and combines with the bonding site of the zirconia composite oxide. Through this bonding, the cations or anions are electrostatically repelled, and the particles constituting the black zirconia composite sintered body can maintain the properties of strength, and weaken the grain boundary strength, which plays a role in improving the machinability.
[0082] For example, Figure 2 As shown in (a), it is considered that the +1-valent cation is combined with another bonding site of the oxygen atom bonded to the metal element (such as Zr, Hf, Y, Nb or Ta) contained in the zirconium oxide composite oxide to replace the aforementioned metal element. Figure 2 In (a), M + Indicates a +1 valent cation.
[0083] In addition, if Figure 2 As shown in (b), it is believed that the -1-valent anion is bound to the OH group of the metal element (such as Zr, Hf, Y, Nb or Ta) contained in the zirconium oxide composite oxide. 2+ Combined form.
[0084] Furthermore, if Figure 2 As shown in (c), it is considered that a -1 valent anion is combined with a cation derived from a metal element (such as Zr, Hf, Y, Nb or Ta) contained in the zirconium oxide composite oxide and combined with other metal elements. Figure 2 In (b) and (c), X - It represents a -1 valent anion.
[0085] exist Figure 2 In (a) to (c), the interaction between the charged points at the grain boundaries and the adsorption sites is schematically represented.
[0086] In addition, since Nb2O5 and / or Ta2O5 act in the direction of coarsening the microstructure and reducing the hardness in the black zirconia composite sintered body, the end-capping element or ion is integrated with Nb2O5 and / or Ta2O5 and acts in the direction of improving the machinability. Therefore, it is speculated that the end-capping element or ion acts in the direction of improving the machinability by integrating with Nb2O5 and / or Ta2O5, having suitable strength and being able to impart excellent machinability, so in addition to being able to shorten the machining time based on machining, it is also possible to suppress the consumption of machining tools, increase the number of machined bodies obtained by continuous machining using one machining tool, and solve the unique problems in the continuous machining of zirconia sintered bodies.
[0087] In the black zirconia composite sintered body of the present invention, the terminal elements or ions function as a free-machining agent as described above, and the strength is not seriously impaired.
[0088] The content of the capping element or ion contained in the black zirconia composite sintered body of the present invention is preferably greater than 0 mol% and less than 5 mol%. From the viewpoint of better machinability and the ability to further increase the number of processed bodies that can be continuously processed with one processing tool, it is more preferably greater than 0.05 mol% and less than 3 mol%, further preferably greater than 0.06 mol% and less than 2.5 mol%, particularly preferably greater than 0.07 mol% and less than 1.0 mol%, and most preferably greater than 0.08 mol% and less than 0.34 mol%.
[0089] In addition, when the capping element or ion contained in the black zirconia composite sintered body of the present invention is a Group 17 element or ion, it is more preferably 0.2 mol% to 5 mol%, more preferably 0.3 mol% to 4 mol%, particularly preferably 0.4 mol% to 3.5 mol%, and most preferably 0.5 mol% to 3.0 mol%, from the viewpoint of better machinability and further increasing the number of processed bodies that can be continuously processed with one processing tool.
[0090] As described above, it is important for the capping element or ion to exist at the grain boundary as a +monovalent cation or a -monovalent anion from the viewpoint of exhibiting appropriate interaction between the charged point at the grain boundary and the adsorption site.
[0091] As the capping element or ion, preferably, an element or its ion belonging to the 2nd to 7th period of the periodic table and having a first ionization energy smaller than that of the 18th group element in the same period, an element or its ion with high electron affinity, a nitrate ion, a hypochlorite ion, a chlorate ion, a perchlorate ion, a bromate ion, a permanganate ion, a metaborate ion, and a cyanide ion.
[0092] As some suitable embodiments, black zirconia composite sintered bodies can be cited, wherein the aforementioned elements or their ions derived from the capping agent are elements or their ions belonging to the 2nd to 7th periods of the periodic table and having a first ionization energy less than that of the 18th group elements of the same period, and / or elements or their ions with high electron affinity.
[0093] As the aforementioned elements belonging to the 2nd to 7th periods of the periodic table and having a first ionization energy smaller than that of the 18th group elements in the same period, Cu, Ag, Li, Na, K, Rb, Cs, Fr, etc. are suitable because they are easier to obtain +1 valent cations and have better machinability.
[0094] As the element with high electron affinity, from the viewpoint of being easier to obtain a -1-valent anion and having better machinability, preferably an element of Group 17. As the element of Group 17, At, I, Br, Cl and F are preferred.
[0095] The first ionization energy is the energy required to remove an electron from a neutral atom and ionize it. The first ionization energy may be the same as the first ionization energy described in "Shriver Atkins Inorganic Chemistry (Volume 1) 4th Edition Part I Fundamentals 1. Atomic Structure". The first ionization energy may be converted to the unit of "KJ / mol" from the unit of "eV" of the first ionization energy described in "Shriver Atkins Inorganic Chemistry (Volume 1) 4th Edition Appendix 2" as 1eV=96.485KJ / mol. The first ionization energy may also be obtained by the photoelectron yield spectroscopy (PYS) method.
[0096] Electron affinity (EA) is the energy released when an electron is introduced into a neutral atom. Electron affinity can be measured by the difference between the ionization potential and the energy gap. The ionization potential is defined as the energy difference between the highest energy occupied orbital in the molecular orbital of a compound and the vacuum energy level, and its value is measured using ultraviolet photoelectron spectroscopy.
[0097] As the first ionization energy and the electron affinity, data stored in the NIST Chemistry WebBook (https: / / webbook.nist.gov / chemistry / ) can also be used (select Ionization Energy or Electron Affinity from Ion energetics properties).
[0098] The first ionization energy and the electron affinity may be measured by appropriately using the above-mentioned methods as long as the ease of forming a +1-valent cation or a -1-valent anion can be compared between other elements to be compared.
[0099] Specific examples of the end-capping element include Cu, Ag, Li, Na, K, Rb, Cs, Fr, At, I, Br, Cl, and F. From the viewpoint of further improving machinability, Cu, Ag, Li, Na, K, Rb, Cs, Fr, I, Br, Cl, and F are preferred.
[0100] In some suitable embodiments, a black zirconia composite sintered body can be cited, wherein the elements derived from the capping agent include at least one element selected from Cu, Ag, Li, Na, K, Rb, Cs, Fr, At, I, Br, Cl and F, and the ions of the aforementioned elements are +1 valent cations or -1 valent anions of at least one selected from Cu, Ag, Li, Na, K, Rb, Cs, Fr, I, Br, Cl and F.
[0101] In other suitable embodiments, a black zirconia composite sintered body may be cited, wherein the element or ion derived from the capping agent includes at least one element or ion selected from Ag, Li, Na, K, Rb, Cs, Fr, At, I, Br, Cl and F.
[0102] The capping element or ion may be used alone or in combination of two or more.
[0103] In the black zirconia composite sintered body of the present invention, the total content of ZrO2 and HfO2 is 78 to 97.5 mol% in the total of 100 mol% of ZrO2, HfO2, the aforementioned stabilizer, Nb2O5 and Ta2O5. From the viewpoint of better strength, it is preferably greater than 79 mol% and less than 96 mol%, more preferably greater than 80 mol% and less than 94 mol%, and further preferably greater than 81 mol% and less than 93 mol%.
[0104] As described above, in the black zirconia composite sintered body of the present invention, Nb2O5 and Ta2O5 act in the direction of coarsening the fine structure and reducing the hardness, and act as a whole with the capping elements or ions to impart excellent machinability. Therefore, although the combined content of ZrO2 and HfO2 is as high as 78 to 97.5 mol%, the machinability is excellent in the sintered body state.
[0105] Examples of stabilizers that can inhibit the phase transition of zirconium oxide include calcium oxide (CaO), magnesium oxide (MgO), yttrium oxide (Y2O3), cerium oxide (CeO2), scandium oxide (Sc2O3), lanthanum oxide (La2O3), erbium oxide (Er2O3), praseodymium oxide (Pr2O3, Pr6O3), and vanadium oxide (Pr2O3). 11), samarium oxide (Sm2O3), europium oxide (Eu2O3), thulium oxide (Tm2O3), gallium oxide (Ga2O3), indium oxide (In2O3) and ytterbium oxide (Yb2O3), etc., and Y2O3 (yttrium oxide) and / or CeO2 are preferred from the viewpoint of better effects of the present invention, especially excellent aesthetics. The aforementioned stabilizer may be used alone or in combination of two or more.
[0106] As described above, since the capping element or ion functions as a whole with Nb2O5 and / or Ta2O5, the effect of the aforementioned stabilizer is not impaired, and thus the aforementioned stabilizer is not particularly limited and achieves the effect of the present invention.
[0107] In the black zirconia composite sintered body of the present invention, the content of the stabilizer capable of inhibiting the phase transformation of zirconia is 1 to 12 mol% in the total of 100 mol% of ZrO2, HfO2, the aforementioned stabilizers, Nb2O5 and Ta2O5. From the perspective of easy acquisition of sufficient machinability, it is preferably from 2 mol% to 10 mol%, from the perspective of better strength, it is more preferably from 3 mol% to 8 mol%, and further preferably from 3.5 mol% to 7.5 mol%.
[0108] As some suitable embodiments, there can be mentioned a black zirconia composite sintered body, in which the stabilizer capable of suppressing the phase transformation of zirconia comprises Y2O3 and / or CeO2, and the total content of Y2O3 and CeO2 is greater than 2 mol% and less than 10 mol%.
[0109] As some other suitable embodiments, there can be mentioned a black zirconia composite sintered body, in which the stabilizer capable of suppressing the phase transformation of zirconia includes Y2O3, and the content of Y2O3 is 2 mol% or more and 10 mol% or less.
[0110] In any of the aforementioned embodiments, the contents of Y2O3 and CeO2 may be appropriately changed within the range described in this specification. For example, from the perspective of achieving better strength, the combined content of Y2O3 and CeO2 may be greater than 2.5 mol % and less than 10 mol %, or may be greater than 3 mol % and less than 9 mol %.
[0111] In the black zirconia composite sintered body of the present invention, the total content of Nb2O5 and Ta2O5 is 1 to 9 mol% in the total of 100 mol% of ZrO2, HfO2, the above-mentioned stabilizer, Nb2O5 and Ta2O5, preferably 1.5 mol% or more and 8.5 mol% or less. From the perspective of functioning in an integrated manner with the end-capping element or ion and having better machinability, it is more preferably 2.5 mol% or more and 8 mol% or less, and further preferably 3 mol% or more and 7 mol% or less. When the total content of Nb2O5 and Ta2O5 is less than 1 mol%, it is difficult to obtain sufficient machinability. In addition, when the total content of Nb2O5 and Ta2O5 exceeds 9 mol%, the resulting black zirconia composite sintered body will have defects, etc., and it is difficult to obtain sufficient physical properties.
[0112] As described above, Nb2O5 and Ta2O5 act in the direction of coarsening the microstructure and reducing the hardness, and act as a whole with the capping elements or ions to impart excellent machinability. In addition, through the interaction with other components (such as TiO2 and Al2O3) added to the black zirconia composite sintered body and the application of HIP, the sintering density can be maximized, and a black zirconia composite sintered body with better appearance design can be easily obtained.
[0113] The content of each component of ZrO2, HfO2, stabilizer, Nb2O5 and Ta2O5 is a ratio when the total of ZrO2, HfO2, stabilizer, Nb2O5 and Ta2O5 is 100 mol%, and the total of ZrO2, HfO2, stabilizer, Nb2O5 and Ta2O5 does not exceed 100 mol%. For example, when the raw material composition contains Nb2O5 and does not contain Ta2O5, the content of each component of ZrO2, HfO2, stabilizer and Nb2O5 refers to the content ratio relative to the total of ZrO2, HfO2, stabilizer and Nb2O5, which is 100 mol%.
[0114] In addition, when the content of the stabilizer is set to A mol % and the total content of Nb2O5 and Ta2O5 is set to B mol %, from the viewpoint of machinability, the ratio of A / B is preferably greater than 0.9 and less than 3, and more preferably greater than 0.95 and less than 2. From the perspective of improving the effect of the capping element or ion acting as a whole with Nb2O5 and / or Ta2O5, imparting better machinability, suppressing the consumption of processing tools, and further increasing the number of processed bodies obtained by continuous processing using one processing tool, it is further preferably greater than 1 and less than 1.6.
[0115] As some suitable embodiments of the present invention, there can be cited a black zirconia composite sintered body, which includes ZrO2, HfO2, a stabilizer capable of inhibiting the phase transition of zirconia, and Nb2O5 and / or Ta2O5,
[0116] In the total of 100 mol % of ZrO2, HfO2, the above-mentioned stabilizer, Nb2O5 and Ta2O5, the total content of ZrO2 and HfO2 is 78 to 97.5 mol %,
[0117] The content of the stabilizer is 1 to 12 mol%.
[0118] The total content of Nb2O5 and Ta2O5 is 1 to 9 mol%.
[0119] The black zirconium oxide composite sintered body further comprises a capping element or ion,
[0120] The stabilizer comprises Y2O3 and / or CeO2,
[0121] The content of the aforementioned end-capping element or ion is greater than 0 mol% and less than 3 mol% relative to 100 mol% of the total of ZrO2, HfO2, the aforementioned stabilizer, Nb2O5 and Ta2O5,
[0122] When the content of the above-mentioned stabilizer is set to A mol % and the total content of Nb2O5 and Ta2O5 is set to B mol %, A / B is greater than or equal to 0.9 and less than or equal to 3.
[0123] As certain embodiments of the present invention, a black zirconia composite sintered body can be cited, which contains, in addition to ZrO2, HfO2, a stabilizer capable of inhibiting the phase transformation of zirconia, Nb2O5 and / or Ta2O5, and a capping element or ion, a zirconia strengthener.
[0124] The zirconia strengthener acts integrally with the capping elements or ions in a black zirconia composite sintered body comprising ZrO2, HfO2, a stabilizer capable of suppressing phase transformation of zirconia, and Nb2O5 and / or Ta2O5, thereby improving the strength of the sintered body.
[0125] In the black zirconia composite sintered body containing zirconia strengthener, the total content of ZrO2 and HfO2, the type and content of stabilizer, the total content of Nb2O5 and Ta2O5, the type and content of capping elements or ions, and the ratio of A / B can also be appropriately changed as described above.
[0126] In the black zirconia composite sintered body containing a zirconia reinforcing agent, from the perspective of suppressing the influence on the black color, the content of the zirconia reinforcing agent is preferably greater than 0 mass% and less than 5.0 mass% relative to the total of 100 mass% of ZrO2, HfO2, a stabilizer capable of suppressing the phase transformation of zirconia, Nb2O5 and Ta2O5. From the perspective of functioning as a whole when combined with a capping element or ion, having excellent machinability and even better strength, it is more preferably greater than 0.01 mass% and less than 4.5 mass%, and further preferably greater than 0.5 mass% and less than 4.0 mass%.
[0127] Examples of the zirconium oxide reinforcing agent include TiO 2 and Al 2 O 3 . The zirconium oxide reinforcing agent may be used alone or in combination of two or more.
[0128] As some suitable embodiments, there can be mentioned a black zirconia composite sintered body, in which the zirconia reinforcing agent includes TiO 2 and the content of TiO 2 is 0.6 to 3.7% by mass.
[0129] As some suitable embodiments, there can be mentioned a black zirconia composite sintered body, which includes ZrO2, HfO2, a stabilizer capable of suppressing the phase transformation of zirconia, and Nb2O5 and / or Ta2O5.
[0130] In the total of 100 mol % of ZrO2, HfO2, the above-mentioned stabilizer, Nb2O5 and Ta2O5, the total content of ZrO2 and HfO2 is 78 to 97.5 mol %,
[0131] The content of the stabilizer is 1 to 12 mol%.
[0132] The total content of Nb2O5 and Ta2O5 is 1 to 9 mol%.
[0133] The black zirconium oxide composite sintered body further comprises a capping element or ion,
[0134] The stabilizer comprises Y2O3 and / or CeO2,
[0135] The zirconium oxide reinforcing agent contains TiO2, and the content of TiO2 is 0.6 to 3.7% by mass.
[0136] The content of the aforementioned end-capping element or ion is greater than 0 mol% and less than 3 mol% relative to 100 mol% of the total of ZrO2, HfO2, the aforementioned stabilizer, Nb2O5 and Ta2O5,
[0137] When the content of the above-mentioned stabilizer is set to A mol % and the total content of Nb2O5 and Ta2O5 is set to B mol %, A / B is greater than or equal to 0.9 and less than or equal to 3.
[0138] The average grain size of the black zirconia composite sintered body of the present invention is preferably 0.5 to 5.0 μm, more preferably 0.5 to 4.5 μm, and even more preferably 1.0 to 4.0 μm from the viewpoint of better machinability and strength. The method for measuring the average grain size is described in the Examples below.
[0139] The average grain size can be measured by adjusting the number of particles so that the number of particles included in the SEM photograph image of one field of view is about 50 or 100 in the method described in the Examples.
[0140] The density of the black zirconia composite sintered body is preferably 5.5 g / cm2 because the higher the density, the fewer internal voids and the higher the strength. 3 More preferably, 5.7 g / cm 3 More preferably, 5.9 g / cm 3 above.
[0141] It is particularly preferred that the black zirconia composite sintered body contains substantially no voids.
[0142] The density of the composite sintered body can be calculated by (mass of the composite sintered body) / (volume of the composite sintered body).
[0143] As another embodiment of the present invention, there is exemplified a method for producing a black zirconia composite sintered body, which comprises:
[0144] A step of producing a formed body using a raw material composition, wherein the raw material composition comprises ZrO2, HfO2, a stabilizer capable of suppressing phase transformation of zirconium oxide, and Nb2O5 and / or Ta2O5,
[0145] In the total of 100 mol % of ZrO2, HfO2, the above-mentioned stabilizer, Nb2O5 and Ta2O5, the total content of ZrO2 and HfO2 is 78 to 97.5 mol %,
[0146] The content of the stabilizer is 1 to 12 mol%.
[0147] The total content of Nb2O5 and Ta2O5 is 1 to 9 mol%.
[0148] The raw material composition further comprises a capping agent; and
[0149] A step of sintering the molded body.
[0150] The raw material composition used in the manufacture of the black zirconia composite sintered body includes ZrO2, HfO2, a stabilizer capable of inhibiting the phase transformation of zirconia, Nb2O5 and / or Ta2O5, and a capping agent. The raw material composition of the black zirconia composite sintered body may be in a dry state, or in a state containing a liquid or in a state contained in a liquid. The raw material composition may be in the form of, for example, powder, granules or granules, paste, slurry, etc.
[0151] The raw material composition includes a capping agent so that the obtained black zirconium oxide composite sintered body includes a capping element or ion. As a capping agent, as long as it is a compound that can become a monovalent ion (+1-valent cation or -1-valent anion) in a solvent containing water, it is not particularly limited, for example, hydroxides, salts, halides (fluorides, chlorides, bromides, iodides), cyanides, etc. containing elements or ions derived from the capping agent can be cited. The capping agent can be used alone or in combination of two or more.
[0152] Examples of the hydroxide containing a capping element or ion include lithium hydroxide, sodium hydroxide, potassium hydroxide, rubidium hydroxide, cesium hydroxide, and francium hydroxide.
[0153] Examples of the salt containing the capping element or ion include carbonates, hydrogen carbonates, nitrates, hypochlorites, chlorites, chlorates, perchlorates, bromates, permanganates, metaborates, sulfide salts, and cyanide salts.
[0154] Examples of the carbonate containing a capping element or ion include lithium carbonate, sodium carbonate, potassium carbonate, rubidium carbonate, francium carbonate, and cesium carbonate.
[0155] Examples of the hydrogen carbonate salt containing a capping element or ion include lithium hydrogen carbonate, sodium hydrogen carbonate, potassium hydrogen carbonate, rubidium hydrogen carbonate, francium hydrogen carbonate, and cesium hydrogen carbonate.
[0156] Examples of nitrates containing a capping element or ion include calcium nitrate, strontium nitrate, iron (II) nitrate, iron (III) nitrate, cobalt (II) nitrate, magnesium nitrate, gallium nitrate, yttrium (III) nitrate, lanthanum (III) nitrate, praseodymium nitrate, neodymium (III) nitrate, manganese (II) nitrate, europium nitrate, copper (II) nitrate, thorium nitrate, aluminum nitrate, nickel (II) nitrate, chromium (III) nitrate, titanium (IV) nitrate, zirconium nitrate, zirconium (IV) nitrate hydrate (ZrO(NO3)2·xH2O), cerium (III) nitrate, tin nitrate, bismuth (III) nitrate, scandium (III) nitrate, indium (III) nitrate, and hafnium (IV) nitrate.
[0157] Examples of the hypochlorite containing a capping element or ion include sodium hypochlorite and calcium hypochlorite.
[0158] Examples of chlorites containing a capping element or ion include sodium chlorite, potassium chlorite, lithium chlorite, calcium chlorite, magnesium chlorite, barium chlorite, copper (II) chlorite, copper (III) chlorite, silver chlorite, and nickel chlorite.
[0159] Examples of the chlorate containing a capping element or ion include calcium chlorate, barium chlorate, cobalt chlorate, nickel chlorate, magnesium chlorate, zinc chlorate, and copper chlorate.
[0160] Examples of the perchlorate containing a capping element or ion include iron (III) perchlorate, barium perchlorate, calcium perchlorate, cobalt perchlorate, nickel perchlorate, magnesium perchlorate, beryllium perchlorate, aluminum perchlorate, and cerium perchlorate.
[0161] Examples of the bromate containing a capping element or ion include neodymium bromate, lanthanum bromate, and praseodymium bromate.
[0162] Examples of permanganate containing a capping element or ion include calcium permanganate (VII), potassium permanganate (VII), sodium permanganate (VII), and the like.
[0163] Examples of the metaborate containing a capping element or ion include sodium metaborate and barium metaborate.
[0164] Examples of the sulfide salt containing a capping element or ion include copper (I) sulfide and the like.
[0165] Examples of the cyanide salt containing a capping element or ion include barium cyanide, sodium cyanide, potassium cyanide, and calcium cyanide.
[0166] Examples of the fluoride containing a terminal element or ion include lithium fluoride, sodium fluoride, potassium fluoride, rubidium fluoride, cesium fluoride, francium fluoride, beryllium fluoride, magnesium fluoride, calcium fluoride, strontium fluoride, barium fluoride, scandium (III) fluoride, yttrium (III) fluoride, lanthanum (III) fluoride, cerium (III) fluoride, neodymium (III) fluoride, titanium (III) fluoride, titanium (IV) fluoride, zirconium (IV) fluoride, hafnium (IV) fluoride, tantalum (V) fluoride, manganese (II) fluoride, manganese (III) fluoride, iron (II) fluoride, iron (III) fluoride, copper (II) fluoride, zinc (II) fluoride, aluminum fluoride, chromium (III) fluoride, bismuth (III) fluoride, indium (III) fluoride, and tin (II) fluoride.
[0167] Examples of the chloride containing a terminal element or ion include zirconium oxychloride, lithium chloride, sodium chloride, potassium chloride, rubidium chloride, cesium chloride, francium chloride, beryllium chloride, magnesium chloride, calcium chloride, strontium chloride, barium chloride, scandium (III) chloride, yttrium (III) chloride, lanthanum (III) chloride, cerium (III) chloride, praseodymium chloride, neodymium (III) chloride, samarium chloride, europium chloride, titanium (III) chloride, titanium (IV) chloride, zirconium (IV) chloride, hafnium (IV) fluoride, tantalum (V) chloride, manganese chloride, iron (II) chloride, iron (III) chloride, cobalt (II) chloride, nickel (II) chloride, copper (I) chloride, copper (II) chloride, zinc (II) chloride, aluminum chloride, gallium chloride, bismuth (III) chloride, indium (I) chloride, indium (III) chloride, and tin (II) chloride.
[0168] Examples of bromides containing a terminal element or ion include lithium bromide, sodium bromide, potassium bromide, rubidium bromide, cesium bromide, francium bromide, beryllium bromide, magnesium bromide, calcium bromide, strontium bromide, barium bromide, scandium (III) bromide, yttrium (III) bromide, cerium (III) bromide, neodymium (III) bromide, titanium (IV) bromide, zirconium (IV) bromide, tantalum (V) bromide, manganese (II) bromide, iron (II) bromide, iron (III) bromide, cobalt (II) bromide, nickel (II) bromide, copper (I) bromide, copper (II) bromide, zinc (II) bromide, chromium (III) bromide, bismuth (III) bromide, vanadium (III) bromide, indium (III) bromide, and tin bromide.
[0169] Examples of the iodide containing a terminal element or ion include lithium iodide, sodium iodide, potassium iodide, rubidium iodide, cesium iodide, francium iodide, beryllium iodide, calcium iodide, magnesium iodide, strontium iodide, barium iodide, scandium (III) iodide, yttrium (III) iodide, lanthanum (III) iodide, cerium (III) iodide, neodymium (III) iodide, titanium (IV) iodide, zirconium (IV) iodide, hafnium (IV) iodide, tantalum (V) iodide, manganese (II) iodide, iron (II) iodide, iron (III) iodide, cobalt (II) iodide, nickel (II) iodide, copper (I) iodide, zinc (II) iodide, aluminum iodide, chromium (III) iodide, vanadium (II) iodide, bismuth (III) iodide, indium (III) iodide, tin (II) iodide, and tin (IV) iodide.
[0170] For ZrO2 and HfO2, commercially available zirconium oxide powder can be used. Examples of commercially available products include zirconium oxide powder (trade name "Zpex (registered trademark)" (content of Y2O3: 3 mol%), "Zpex (registered trademark) 4" (content of Y2O3: 4 mol%), "Zpex (registered trademark) 4Smile (registered trademark)" (content of Y2O3: 5.5 mol%), "TZ-3Y" (content of Y2O3: 3 mol%), "TZ-3YS" (content of Y2O3: 3 mol%), "TZ-4YS" (content of Y2O3: 4 mol%), "TZ-6Y" (content of Y2O3: 6 mol%), "TZ-6YS" (content of Y2O3: 6 mol%), "TZ-8YS" (content of Y2O3: 8 ... Z-10YS" (content of Y2O3: 10 mol%), "TZ-3Y-E" (content of Y2O3: 3 mol%), "TZ-3YS-E" (content of Y2O3: 3 mol%), "TZ-3YB-E" (content of Y2O3: 3 mol%), "TZ-3YSB-E" (content of Y2O3: 3 mol%), "TZ-3YB" (content of Y2O3: 3 mol%), "TZ-3YSB" (content of Y2O3: 3 mol%), "TZ-3Y20AB" (content of Y2O3: 3 mol%), "TZ-8YSB" (content of Y2O3: 8 mol%), "TZ-0" (content of Y2O3: 0 mol%); all of the above are manufactured by Tosoh Corporation), etc. The aforementioned commercially available zirconia powder also contains HfO2. As a commercial product, a product containing Y2O3 may also be used. As the zirconium oxide powder, in the raw material composition of the present invention, a zirconium oxide powder in which Y2O3 is uniformly dispersed and solid-dissolved, such as the aforementioned commercial product TZ series (part of the product name contains "TZ"), may also be used.
[0171] The method for producing the zirconium oxide powder is not particularly limited, and for example, a known method such as a fracturing process in which coarse particles are crushed into fine powder, or a deposition process in which atoms or ions form nuclei and synthesize the particles through a growth process can be used.
[0172] The type of zirconium oxide powder in the raw material composition is not particularly limited. The zirconium oxide powder contains ZrO2 and HfO2. When no stabilizer is contained or when the content of the stabilizer is increased as required, stabilizer particles can be added separately. The stabilizer particles are not particularly limited as long as the content of the stabilizer contained in the black zirconium oxide composite sintered body can be adjusted to the above-specified range.
[0173] As the particles of the stabilizer, for example, a commercially available product may be used, or a powder of a commercially available product may be pulverized using a known pulverizing and mixing device (such as a ball mill) and then used.
[0174] The aforementioned stabilizer may be any one of a stabilizer that is insoluble in ZrO 2 and HfO 2 and a stabilizer that is soluble in ZrO 2 and HfO 2 .
[0175] In some suitable embodiments, a method for producing a black zirconia composite sintered body can be cited, wherein, in the raw material composition, from the aspect of being a reason for easily obtaining the target black zirconia composite sintered body, the stabilizer (suitably Y2O3) includes a stabilizer that is not soluble in ZrO2 and HfO2. For example, it can be confirmed by an X-ray diffraction (XRD; X-Ray Diffraction) pattern that the stabilizer includes a stabilizer that is not soluble in zirconia.
[0176] When a peak derived from a stabilizer is confirmed in the XRD pattern of the raw material composition or the molded body, a stabilizer that is not solid-soluble in ZrO 2 and HfO 2 exists in the raw material composition or the molded body.
[0177] When the entire amount of stabilizer is solid-dissolved in ZrO2 and HfO2, the peak derived from the stabilizer cannot be confirmed in the XRD pattern. However, depending on conditions such as the crystal state of the stabilizer, even if there is no peak of the stabilizer in the XRD pattern, the stabilizer may sometimes not be solid-dissolved in ZrO2 and HfO2.
[0178] The case where the stabilizer contains a stabilizer that is not soluble in ZrO 2 and HfO 2 is described below using yttrium oxide as an example.
[0179] In the raw material composition or the molded body of the present invention, the existence ratio of yttrium oxide that is not dissolved in ZrO2 and HfO2 (hereinafter sometimes referred to as "undissolved yttrium oxide") is y It can be calculated based on the following mathematical formula (1).
[0180] f y =I 29 / (I 28 +I 29 +I 30 )×100
[0181] (where f y Indicates the proportion of undissolved yttrium oxide (%). In XRD measurement, I 28 The area intensity of the peak near 2θ = 28° where the main peak of the monoclinic system appears, I 29 The area intensity of the peak near 2θ = 29° where the main peak of yttrium oxide appears, I 30 It indicates the area intensity of the peak near 2θ=30° where the main peak of the tetragonal or cubic system appears.
[0182] In addition, when a stabilizer other than yttrium oxide is used simultaneously, by replacing I 29 Substituting the peaks of other stabilizers can also be used to calculate the undissolved existence rate of stabilizers other than yttrium oxide.
[0183] From the viewpoint of easily obtaining the target black zirconia composite sintered body, the existence ratio of undissolved yttrium oxide is f y It is preferably greater than 0%, more preferably 1% or more, further preferably 2% or more, and particularly preferably 3% or more. y The upper limit of γ may be, for example, 25% or less, but it preferably depends on the content of yttrium oxide in the raw material composition or the molded body.
[0184] For example, when the content of yttrium oxide in the raw material composition or the molded body of the present invention is 3 mol% or more and 8 mol% or less, it is as follows.
[0185] When the content of yttrium oxide is 3 mol% or more and less than 4.5 mol%, f y When the content of yttrium oxide is 4.5 mol% or more and less than 5.8 mol%, f y When the content of yttrium oxide is 5.8 mol% or more and 8 mol% or less, f y It can be set to 25% or less.
[0186] For example, when the content of yttrium oxide is 3 mol% or more and less than 4.5 mol%, f y It is preferably 2% or more, more preferably 3% or more, further preferably 4% or more, and particularly preferably 5% or more.
[0187] When the content of yttrium oxide is 4.5 mol% or more and less than 5.8 mol%, f y It is preferably 3% or more, more preferably 4% or more, further preferably 5% or more, further preferably 6% or more, and particularly preferably 7% or more.
[0188] When the content of yttrium oxide is 5.8 mol% or more and 8 mol% or less, f y It is preferably 4% or more, more preferably 5% or more, further preferably 6% or more, further preferably 7% or more, and particularly preferably 8% or more.
[0189] In the raw material composition or the molded body of the present invention, the stabilizer may not be solid-dissolved in ZrO2 and HfO2 at all. It should be noted that in the present invention, the so-called solid-dissolved stabilizer means, for example, that the elements (atoms) contained in the stabilizer are solid-dissolved in ZrO2 and HfO2.
[0190] The Nb2O5 and / or Ta2O5 added to the raw material composition of the present invention is not particularly limited as long as the content of Nb2O5 and / or Ta2O5 contained in the black zirconia composite sintered body can be adjusted to the above-mentioned specified range. Nb2O5 and / or Ta2O5 are not particularly limited, for example, commercial products can be used, and powders of commercial products can also be crushed using a known crushing and mixing device (ball mill, etc.) and then used.
[0191] As a process for preparing the raw material composition, for example, there can be cited a method of wet-mixing the raw materials of the aforementioned raw material composition (ZrO2, HfO2, stabilizer, Nb2O5 and / or Ta2O5, a capping agent (for example, a compound that can become a monovalent ion in a solvent containing water), and further a zirconium oxide reinforcing agent as required) in a solvent containing water to obtain the raw material composition.
[0192] The method for wet mixing the aforementioned raw materials in a solvent containing water is not particularly limited. For example, the raw materials can be wet-mixed by a known pulverizing and mixing device (ball mill, etc.) to form a slurry, and then the slurry is dried and granulated to prepare a granular raw material composition.
[0193] In the wet mixing step, additives such as a binder, a plasticizer, a dispersant, an emulsifier, a defoamer, a pH adjuster, and a lubricant may be further contained. The additives may be used alone or in combination of two or more.
[0194] The aforementioned binder may be prepared by adding a primary powder of a mixture of ZrO2, HfO2, Y2O3, Nb2O5 and / or Ta2O5 and a capping agent to water to prepare a slurry, and then adding the primary powder to the crushed slurry.
[0195] The aforementioned adhesive is not particularly limited, and known adhesives can be used. As the adhesive, for example, polyvinyl alcohol-based adhesives, acrylic adhesives, wax-based adhesives (paraffin, etc.), methylcellulose, carboxymethylcellulose, polyvinyl butyral, polymethyl methacrylate, ethylcellulose, polyethylene, polypropylene, ethylene-vinyl acetate copolymer, polystyrene, atactic polypropylene, methacrylic resins, etc. can be cited.
[0196] Examples of the plasticizer include polyethylene glycol, glycerin, propylene glycol, and dibutyl phthalate.
[0197] Examples of the dispersant include ammonium polycarboxylates (triammonium citrate, etc.), ammonium polyacrylates, acrylic copolymer resins, acrylate copolymers, polyacrylic acid, bentonite, carboxymethyl cellulose, anionic surfactants (e.g., polyoxyethylene alkyl ether phosphates such as polyoxyethylene lauryl ether phosphate, etc.), nonionic surfactants, olein, amine salt-type surfactants, oligosaccharide alcohols, and stearic acid.
[0198] Examples of the emulsifier include alkyl ethers, phenyl ethers, and sorbitan derivatives.
[0199] Examples of the defoaming agent include alcohol, polyether, silicone, wax, and the like.
[0200] Examples of the pH adjuster include ammonia, ammonium salts (including ammonium hydroxide such as tetramethylammonium hydroxide), and the like.
[0201] Examples of the lubricant include polyoxyethylene alkyl ether and wax.
[0202] The solvent used for wet mixing is not particularly limited as long as it contains water, and an organic solvent, a mixed solvent of water and an organic solvent, or water alone may be used.
[0203] Examples of the organic solvent include ketone solvents such as acetone and ethyl methyl ketone; alcohol solvents such as ethanol, 1-propanol, 2-propanol, 2-methyl-2-propanol, glycerol, diglycerol, polyglycerol, propylene glycol, dipropylene glycol, polypropylene glycol, ethylene glycol, diethylene glycol, polyethylene glycol, polyethylene glycol monomethyl ether, 1,2-pentanediol, 1,2-hexanediol, and 1,2-octanediol; and the like.
[0204] The raw material composition of the black zirconium oxide composite sintered body used in the present invention may also contain other components besides ZrO2, Y2O3, Nb2O5, Ta2O5, a capping agent, and a zirconium oxide reinforcing agent as required, as long as the effect of the present invention is achieved. Examples of the other components include colorants (pigments and composite pigments), fluorescent agents, SiO2, etc. The other components may be used alone or in combination of two or more.
[0205] Examples of the pigment include oxides of at least one element selected from V, Cr, Mn, Fe, Co, Ni, Zn, Y, Zr, Sn, Sb, Bi, Ce, Pr, Sm, Eu, Gd, Tb, and Er (specifically, NiO, Cr2O3, etc.), preferably oxides of at least one element selected from V, Cr, Mn, Fe, Co, Ni, Zn, Y, Zr, Sn, Sb, Bi, Ce, Pr, Sm, Eu, Gd, and Tb, and more preferably oxides of at least one element selected from V, Cr, Mn, Fe, Co, Ni, Zn, Y, Zr, Sn, Sb, Bi, Ce, Sm, Eu, Gd, and Tb. However, Y2O3 and CeO2 may be removed from the pigment.
[0206] Examples of the composite pigment include (Zr, V)O2, Fe(Fe, Cr)2O4, (Ni, Co, Fe)(Fe, Cr)2O4·ZrSiO4, and (Co, Zn)Al2O4.
[0207] Examples of the fluorescent agent include Y2SiO5:Ce, Y2SiO5:Tb, (Y, Gd, Eu)BO3, Y2O3:Eu, YAG:Ce, ZnGa2O4:Zn, BaMgAl 10 O 17 :Eu et al.
[0208] Next, the obtained raw material composition is molded to produce a molded body. The molding method is not particularly limited, and a known method (such as press molding) can be used.
[0209] When the zirconia molded body is produced by a method including the step of press-molding the raw material composition, the specific method of press-molding is not particularly limited, and a known press-molding machine can be used for the press-molding. Specific methods of press-molding include, for example, uniaxial pressing.
[0210] The pressurization pressure is appropriately set to an optimal value according to the size of the target molded body, the porosity, the biaxial bending strength, and the particle size of the raw material powder, and is generally 5 MPa or more and 1000 MPa or less. By increasing the pressurization pressure during molding in the aforementioned manufacturing method, the pores of the obtained molded body are further filled, the porosity can be set lower, and the density of the molded body can be increased. In addition, in order to increase the density of the obtained zirconia molded body, cold isostatic pressing (CIP) treatment can be further performed after uniaxial pressing.
[0211] Next, the obtained compact is sintered.
[0212] The term "molded body" refers to a molded body that has not reached any of the semi-sintered state (pre-fired state) and the sintered state. That is, the molded body is formed into a molded body but is not fired, and is distinguished from a pre-fired body and a sintered body in this respect.
[0213] The sintering temperature (maximum sintering temperature) for obtaining the black zirconia composite sintered body is, for example, preferably 1300°C or higher, more preferably 1350°C or higher, further preferably 1400°C or higher, further preferably 1450°C or higher, and particularly preferably 1500°C or higher. In addition, the sintering temperature is, for example, preferably 1680°C or lower, more preferably 1650°C or lower, and further preferably 1600°C or lower. As the method for producing the black zirconia composite sintered body of the present invention, it is preferred that the formed body be sintered at a maximum sintering temperature of 1400 to 1680°C. The aforementioned maximum sintering temperature is preferably a temperature in the atmosphere.
[0214] The holding time (retention time) at the maximum sintering temperature also depends on the temperature, but is preferably less than 30 hours, more preferably less than 20 hours, further preferably less than 10 hours, further preferably less than 5 hours, particularly preferably less than 3 hours, and most preferably less than 2 hours. Furthermore, the holding time may also be set to less than 25 minutes, less than 20 minutes or less than 15 minutes. In addition, the holding time is preferably more than 1 minute, more preferably more than 5 minutes, and more preferably more than 10 minutes. According to the manufacturing method of the present invention, according to the content of the stabilizer, a black zirconium oxide composite sintered body with excellent bending strength and machinability can be produced. In addition, as long as the effect of the present invention can be obtained, the sintering time can also be shortened. By shortening the sintering time, production efficiency can be improved while reducing energy costs.
[0215] In the method for producing a black zirconia composite sintered body of the present invention, when the molded body is sintered, the heating rate is not particularly limited, but is preferably 0.1°C / min or more, more preferably 0.2°C / min or more, and further preferably 0.5°C / min or more. In addition, the heating rate is preferably 50°C / min or less, more preferably 30°C / min or less, and further preferably 20°C / min or less. By making the heating rate above the lower limit, productivity is improved.
[0216] In the step of sintering the molded body, a general zirconia sintering furnace can be used. As a zirconia sintering furnace, a commercial product can also be used. As commercial products, Noritake Katana (registered trademark) F-1, F-1N, F-2 (all from SK Medical Electronics Co., Ltd.) and the like can be cited.
[0217] In the method for producing a black zirconia composite sintered body, a black zirconia composite sintered body can also be obtained by sintering a molded body to which a black pigment is added.
[0218] Examples of the black pigment include black organic pigments, mixed color organic pigments, and inorganic pigments.
[0219] Examples of black organic pigments include carbon black, perylene black, aniline black, and benzophenone pigments, which may be coated with a resin.
[0220] Examples of the mixed color organic pigment include a pigment obtained by mixing two or more pigments of red, blue, green, purple, yellow, magenta, and / or cyan to produce a pseudo black color.
[0221] Examples of black inorganic pigments include graphite; fine particles of metals such as titanium, copper, iron, manganese, cobalt, chromium, nickel, zinc, calcium, and silver; metal oxides; metal composite oxides; metal sulfides; metal nitrides; metal oxynitrides; and metal carbides.
[0222] However, when a pigment containing titanium is used as the black pigment, the total content of titanium is preferably not more than 5.0 mass % which is the upper limit of the content of the zirconium oxide reinforcing agent TiO 2 .
[0223] In addition, in addition to the method of adding black pigment to the molded body, it is preferred that the molded body be reduction-fired in addition to sintering at the above-mentioned maximum sintering temperature; or instead of the method of adding black pigment to the molded body, it is preferred that the molded body be reduction-fired in addition to sintering at the above-mentioned maximum sintering temperature.
[0224] As some suitable embodiments, there is provided a method for producing a black zirconia composite sintered body, wherein the step of sintering the formed body includes a step of performing reduction sintering in addition to sintering at the aforementioned maximum sintering temperature.
[0225] The reduction sintering process is not particularly limited as long as it is performed in a reducing atmosphere, and an example thereof is a process of performing a hot isostatic pressing (HIP) treatment in a reducing atmosphere. By performing the HIP treatment in a reducing atmosphere, a black zirconia composite sintered body can be obtained by causing blackening due to oxygen defects. In addition, the strength of the black zirconia composite sintered body can be further improved by the HIP treatment.
[0226] Hereinafter, the sintered body obtained by sintering at the above-mentioned maximum sintering temperature is referred to as a "primary sintered body", and the sintered body after HIP treatment is referred to as a "HIP treatment sintered body".
[0227] The HIP treatment can be performed using a known hot isostatic pressing (HIP) apparatus.
[0228] The temperature of the HIP treatment is not particularly limited, but from the perspective of obtaining a dense black zirconia composite sintered body with high strength, the HIP temperature is preferably 1200° C. or higher, more preferably 1300° C. or higher, and further preferably 1400° C. or higher. In addition, the HIP temperature is preferably 1700° C. or lower, more preferably 1650° C. or lower, and further preferably 1600° C. or lower.
[0229] In the method for producing a black zirconia composite sintered body of the present invention, when the primary sintered body is subjected to HIP treatment, the HIP pressure is not particularly limited. From the perspective of being able to obtain a dense sintered body with high strength, the HIP pressure is preferably 100 MPa or more, more preferably 125 MPa or more, and further preferably 130 MPa or more. In addition, the upper limit of the HIP pressure is not particularly limited, and can be, for example, 400 MPa or less, 300 MPa or less, and further 200 MPa or less.
[0230] In the method for producing a black zirconia composite sintered body of the present invention, when the primary sintered body is subjected to HIP treatment, the heating rate is not particularly limited, but is preferably 0.1°C / min or more, more preferably 0.2°C / min or more, and further preferably 0.5°C / min or more. In addition, the heating rate is preferably 50°C / min or less, more preferably 30°C / min or less, and further preferably 20°C / min or less. By making the heating rate above the lower limit, productivity is improved.
[0231] In the method for producing a black zirconia composite sintered body of the present invention, when the primary sintered body is subjected to HIP treatment, the HIP time is not particularly limited. From the perspective of obtaining a high-strength and dense black zirconia composite sintered body, the HIP treatment time is preferably 5 minutes or more, more preferably 10 minutes or more, and further preferably 30 minutes or more. In addition, the HIP treatment time is preferably 10 hours or less, more preferably 6 hours or less, and further preferably 3 hours or less.
[0232] In the method for manufacturing a black zirconia composite sintered body of the present invention, when the aforementioned primary sintered body is subjected to HIP treatment under a reducing atmosphere, the pressure medium is not particularly limited. From the perspective of having a low impact on zirconia, the pressure medium can be selected from at least one of inert gases (such as nitrogen, argon, etc.).
[0233] In the reduction calcination step, the reduction calcination is preferably performed in the presence of carbon from the viewpoint of improving the efficiency of calcination in a reducing atmosphere, lowering the L* value of the composite sintered body, and obtaining a darker black zirconia composite sintered body.
[0234] The carbon used in the step of performing the reduction calcination is not particularly limited, and examples thereof include Referthermo (general-purpose thermal history sensor, an organic component (organic binder (PVA / PEG system)) and the like.
[0235] The black zirconia composite sintered body of the present invention is not particularly limited as long as it can achieve the effects of the present invention, and may be a primary sintered body or a HIP-treated sintered body.
[0236] The black zirconia composite sintered body of the present invention is a sintered body, but has excellent machinability, so it is not necessary to machine a semi-sintered pre-calcined body in a ground state and then sinter it to obtain a sintered body.
[0237] On the other hand, as a method for producing a black zirconia composite sintered body, a method may be adopted in which a molded body obtained using the raw material composition is pre-sintered to produce a semi-sintered pre-sintered body, and the unprocessed pre-sintered body is machined to produce a sintered body.
[0238] As some other embodiments, there can be cited a method for producing a black zirconia composite sintered body, which includes: a step of preparing a formed body using the above-mentioned raw material composition, a step of pre-firing the obtained formed body to obtain a zirconia calcined body (pre-firing step), and a step of sintering the zirconia calcined body.
[0239] In order to reliably perform agglomeration, the firing temperature (pre-firing temperature) in the pre-firing step is, for example, preferably 800° C. or higher, more preferably 900° C. or higher, and further preferably 950° C. or higher.
[0240] The calcining temperature is preferably, for example, 1200° C. or less, more preferably 1150° C. or less, and further preferably 1100° C. or less. The calcining temperature is preferably, for example, 800° C. to 1200° C. It is considered that at such a calcining temperature, the stabilizer will not be dissolved to a large extent in the calcining step.
[0241] The calcined zirconium oxide of the present invention refers to a state in which ZrO2 particles are necked (fixed) to each other and the ZrO2 particles (powder) are not completely sintered (semi-sintered state).
[0242] The density of the calcined zirconium oxide is preferably 2.7 g / cm 3 In addition, the density of the zirconia calcined body is preferably 4.0 g / cm 3 Below, more preferably 3.8 g / cm 3 Below, more preferably 3.6 g / cm 3When the density is within this range, processing can be easily performed. The density of the calcined body can be calculated, for example, in the form of (mass of the calcined body) / (volume of the calcined body).
[0243] The three-point bending strength of the calcined zirconium oxide body is preferably 15 to 70 MPa, more preferably 18 to 60 MPa, and even more preferably 20 to 50 MPa.
[0244] The bending strength can be measured as follows: using a test piece of thickness 5mm×width 10mm×length 50mm, except for the size of the test piece, the test is performed in accordance with ISO 6872:2015. The surface of the test piece and the C surface (the surface obtained by chamfering the corner of the test piece at an angle of 45°) are surface-finished along the length direction using 600 sandpaper. The test piece is configured in a manner that the widest surface faces the vertical direction (load direction). In the bending test measurement, the span is set to 30mm and the crosshead speed is set to 1.0mm / minute.
[0245] The step of sintering the zirconia calcined body can be performed by the same method and conditions (temperature, pressure, etc.) as the step of sintering the molded body. Therefore, in the embodiment of the manufacturing method using the zirconia calcined body, the "molded body" may be replaced with the "calcined body".
[0246] The black zirconia composite sintered body of the present invention has excellent strength. The biaxial bending strength of the black zirconia composite sintered body of the present invention is preferably 300 MPa or more, more preferably 350 MPa or more, further preferably 400 MPa or more, further preferably 450 MPa or more, and particularly preferably 500 MPa or more. By making the black zirconia composite sintered body of the present invention have such biaxial bending strength, for example, breakage can be suppressed. There is no particular restriction on the upper limit of the biaxial bending strength, but the biaxial bending strength can be set to, for example, 1200 MPa or less, and further 1000 MPa or less. It should be noted that the biaxial bending strength of the black zirconia composite sintered body can be measured according to ISO 6872:2015.
[0247] The black zirconia composite sintered body of the present invention preferably has a desired color tone from the viewpoint of excellent design. The color tone can be evaluated by L*, |a*|, and |b*|.
[0248] L*, |a*| and |b*| can be calculated by measuring L*, a*, and b* based on the L*a*b* colorimetric system (JIS Z 8781-4:2013 Colorimetry - Part 4: CIE 1976 L*a*b* color space) in a measurement sample having a diameter of 15 mm and a thickness of 1.2 mm using, for example, a spectrophotometer "CM-3610A" manufactured by Konica Minolta Co., Ltd. under the conditions of D65 light source, measurement mode SCI, and measurement diameter / illumination diameter = φ8 mm / φ11 mm.
[0249] Regarding hue, specifically, for the black zirconia composite sintered body of the present invention, in a sample with a diameter of 15 mm and a thickness of 1.2 mm, the background (underpad) of the sample is set to white (relative to the sample, the side opposite to the hue measuring device is set to white), and L* is preferably below 60, more preferably below 55, and further preferably below 50.
[0250] Furthermore, under the above-mentioned sample and measurement conditions, |a*| is preferably 3 or less, more preferably 2 or less, and even more preferably 1 or less.
[0251] Furthermore, under the above-mentioned sample and measurement conditions, |b*| is preferably 3 or less, more preferably 2.5 or less, and even more preferably 2 or less.
[0252] Some suitable embodiments include a black zirconia composite sintered body having L* of 60 or less, |a*| of 3 or less, and |b*| of 3 or less under the above-mentioned sample and measurement conditions.
[0253] As some other suitable embodiments, there can be mentioned a black zirconia composite sintered body, in which, under the above-mentioned sample and measurement conditions, L* is 50 or less, |a*| is 1 or less, and |b*| is 2 or less.
[0254] By setting the L*, |a*| and |b*| within the above ranges, a black zirconia composite sintered body having excellent design properties can be obtained.
[0255] As some suitable embodiments, from the perspective of easily obtaining a more excellent appearance design, a black zirconia composite sintered body can be cited, in which the color values obtained by measuring the color of a sample with a diameter of 15 mm and a thickness of 1.2 mm against a white background of the L*a*b* color system are L*≤60, |a*|≤3 and |b*|≤3.
[0256] From the viewpoint of excellent appearance design, the black zirconia composite sintered body of the present invention preferably has a chroma C* of 10 or less, more preferably 8 or less, and even more preferably 6 or less, calculated from a* and b* obtained by measuring the color using a sample with a diameter of 15 mm and a thickness of 1.2 mm on a white background of the L*a*b* colorimetric system.
[0257] For C*, the chroma C* can be calculated based on the average value of a* and b* obtained by the above method: * ) 2 +(b * ) 2 ) 1 / 2 .
[0258] The thermal expansion coefficient (CTE) of the black zirconia composite sintered body of the present invention is preferably 8×10 -6 / ℃~13×10 -6 / °C, more preferably 8.5×10 -6 / ℃~12×10 -6 / °C, more preferably 9×10 -6 / ℃~11×10 -6 / ℃.
[0259] Since the coefficient of thermal expansion (CTE) of the black zirconia composite sintered body of the present invention is within the aforementioned range, it can be suitably used in combination with a metal material.
[0260] The coefficient of thermal expansion (CTE) can be measured in accordance with ISO 6872:2015, with the analysis temperature range being 25° C. to 500° C., for example, at a heating rate of 5° C. / min.
[0261] In addition, the black zirconia composite sintered body of the present invention is particularly suitable for use in zirconia components that require a different shape or a complex shape and strength.
[0262] Compared with sintered bodies manufactured only by existing manufacturing methods (injection molding, CIP, casting or 3D printing, etc.), the black zirconia composite sintered body of the present invention can directly process the sintered body. Therefore, it is economical to obtain the desired zirconia component in a short time, and in the case of complex-shaped parts that are difficult to manufacture by conventional manufacturing methods, it is not necessary to obtain multiple components by mechanical interlocking, so that a zirconia component with high strength can be obtained. Furthermore, since the sintered body can be directly processed, when dimensional accuracy is required, a sintering process is not required, there is no uneven sintering shrinkage, and the zirconia component can be obtained with high precision. In addition, mechanical processing can be performed using commercially available mechanical processing equipment, for example.
[0263] The black zirconia composite sintered body of the present invention can be used, specifically, for jewelry decoration purposes (brooches, tie pins, handbag metal parts, bracelets, etc.), engine components and interior components of mobile vehicles such as airplanes and automobiles, frame materials for display panels, building components, portable device components, high-end daily-use components, watch components (watch straps, inlaid glass grooves, dials, watch cases, etc.), frames of portable electronic devices (such as smart phones), lighter housings, cosmetic housings, mobile phone housings, earphone housings and other exterior components, electrical product components, household product components, various product labels, and toy parts.
[0264] Furthermore, the present zirconia component may be used as a composite component by fitting it with a different type of material.
[0265] The present invention includes various embodiments in which all or part of the above-described configurations are combined within the scope of the technical concept of the present invention as long as the effects of the present invention are achieved.
[0266] Example
[0267] Hereinafter, the present invention will be further specifically described by giving examples, but the present invention is not limited to these examples, and a person with common knowledge in the art can make various modifications within the scope of the technical concept of the present invention. It should be noted that in the following examples and comparative examples, the average particle size is the average primary particle size, which can be obtained by a laser diffraction scattering method. Specifically, a laser diffraction particle size distribution measuring device (SALD-2300: manufactured by Shimadzu Corporation) can be used to measure a 0.2% sodium hexametaphosphate aqueous solution as a dispersion medium on a volume basis.
[0268] [Examples 1 to 17 and Comparative Examples 1 to 4]
[0269] The measurement samples of the respective examples and comparative examples were produced through the steps of producing a granular raw material composition, producing a compact, and producing a sintered body (producing a primary sintered body and HIP treatment).
[0270] [Preparation of Granular Raw Material Composition]
[0271] In order to prepare the granular raw material composition of each embodiment and comparative example, commercially available ZrO2 powder, Y2O3 powder, Nb2O5 powder, Ta2O5 powder, and end-capping agent, and further zirconium oxide reinforcing agent powder (TiO2 powder and / or Al2O3 powder) as required are mixed to form the composition described in Table 1 and Table 2, water is added to prepare slurry, and wet pulverization and mixing are carried out with a ball mill until the average particle size becomes less than 0.13μm. After adding a binder to the pulverized slurry, it is dried with a spray dryer to prepare a granular raw material composition (hereinafter also referred to as "raw material composition") for the manufacture of the molded body described later. The above-mentioned average particle size is a value measured by a laser diffraction particle size distribution measuring device (SALD-2300: manufactured by Shimadzu Corporation) using a 0.2% sodium hexametaphosphate aqueous solution as a dispersion medium and measured on a volume basis.
[0272] It should be noted that in Example 17, TZ-3Y (Y2O3 content: 3 mol%):TZ-6Y (Y2O3 content: 6 mol%) = 18.7:81.3 were mixed, and the ratio of each component was adjusted to become the blending ratio described in Table 1.
[0273] [Production of Molded Body]
[0274] For each of the Examples and Comparative Examples, a pellet-shaped molded body and a block-shaped molded body were produced as follows to obtain sintered body samples for strength evaluation and processability evaluation.
[0275] For the pellet-shaped compact, a cylindrical mold with a diameter of 19 mm was used, and the raw material composition was placed in the mold so that the thickness of the black zirconia composite sintered body after sintering was 1.2 mm.
[0276] Next, the raw material composition was press-formed at a surface pressure of 200 MPa using a uniaxial press-forming machine to produce a pellet-shaped compact.
[0277] In addition, for the block-shaped molded body, the raw material composition was placed in a mold with an inner size of 19 mm×18 mm so that the height of the black zirconia composite sintered body after sintering was 14.5 mm.
[0278] Next, the raw material composition was press-formed at a surface pressure of 200 MPa using a uniaxial press-forming machine to produce a block-shaped compact.
[0279] [Production of primary sintered body]
[0280] The obtained particle-shaped and block-shaped formed bodies were kept in the atmosphere at the firing temperature described in Tables 1 and 2 for 2 hours using the sintering furnace "Noritake Katana (registered trademark) F-1" manufactured by SK Medical Electronics Co., Ltd., thereby obtaining particle-shaped and block-shaped zirconia sintered body (primary sintered body) samples.
[0281] [Production of black zirconia composite sintered body (HIP treatment sintered body)]
[0282] The obtained particle-shaped and block-shaped zirconia sintered bodies (primary sintered bodies) were retained for 2 hours at 150 MPa under the HIP temperature and referthermo conditions described in Tables 1 and 2 using a HIP device "O2-Dr.HIP" manufactured by Kobe Steel, Ltd. Using argon as a pressure medium, the particles and block-shaped black zirconia composite sintered bodies (HIP-treated sintered bodies) were obtained. The size of the obtained samples was 15 mm in diameter × 1.2 mm in thickness for the particle shape and 15.7 mm in width × 16.5 mm in length × 14.5 mm in height for the block shape.
[0283] It should be noted that the content of each component of the sintered body in Table 1 and Table 2 is a value calculated from the amount of raw materials charged.
[0284] The contents (mol %) of the terminal elements or ions in Tables 1 and 2 are external addition ratios relative to 100 mol % of the total of ZrO 2 , HfO 2 , the aforementioned stabilizers, Nb 2 O 5 and Ta 2 O 5 .
[0285] The contents (mol%) of ZrO2, HfO2, the aforementioned stabilizer, Nb2O5, and Ta2O5 in Tables 1 and 2 are the contents of each component in the total of 100 mol% of ZrO2, HfO2, the aforementioned stabilizer, Nb2O5, and Ta2O5. Only for ZrO2 and HfO2, it is expressed as the total content of ZrO2 and HfO2.
[0286] The contents (mass %) of TiO 2 and Al 2 O 3 in Tables 1 and 2 are external addition rates relative to the total of 100 mass % of ZrO 2 , HfO 2 , the aforementioned stabilizers, Nb 2 O 5 and Ta 2 O 5 .
[0287] A / B in Tables 1 and 2 represents the ratio of A to B when the content of Y2O3 is A mol% and the total content of Nb2O5 and Ta2O5 is B mol%.
[0288] [Evaluation of color tone of black zirconia composite sintered body]
[0289] The samples (about 15 mm in diameter×1.2 mm in thickness) of the particle-shaped black zirconia composite sintered bodies (HIP-treated sintered bodies) of the Examples and Comparative Examples were used as they were and the color tone was evaluated by the following method (n=3).
[0290] The spectrophotometer "CM-3610A" manufactured by Konica Minolta Co., Ltd. was used to measure L*, a*, and b* based on D65 light source, measurement mode SCI, measurement diameter / illumination diameter = φ8 mm / φ11 mm, the background (underlay) of the sample was set to white (with respect to the sample, the side opposite to the measurement device was set to white), and the L*a*b* color system (JIS Z 8781-4:2013 Colorimetry - Part 4: CIE1976 L*a*b* color space).
[0291] In the measurement, a white background (underlying material) was used as a shielding ratio test paper used for the measurement of coating materials described in JIS K 5600-4-1:1999.
[0292] The average value of L*, the average value of a*, and the average value of b* of each sample are shown in Tables 1 and 2 as results.
[0293] [Strength evaluation of black zirconia composite sintered body]
[0294] The samples of the particle-shaped black zirconia composite sintered bodies (HIP-treated sintered bodies) of the examples and comparative examples were used directly, and the biaxial bending strength (n=5) was measured according to ISO6872:2015 using a universal testing machine "AGS-X" (manufactured by Shimadzu Corporation) with the crosshead speed set to 1.0 mm / min. The average values are shown in Tables 1 and 2 as the measurement results. As for the strength, 300 MPa or more was considered acceptable.
[0295] [Method for measuring average grain size in sintered body]
[0296] In the particle-shaped black zirconia composite sintered body (HIP-treated sintered body) of each example and comparative example, a surface image was obtained using a scanning electron microscope (trade name "VE-9800", manufactured by Keyence Co., Ltd.). After recording the grain boundaries of each crystal particle on the obtained image, the average grain size was calculated by image analysis.
[0297] In the measurement of the average grain size, the image analysis software (trade name "Image-Pro Plus", manufactured by Bodong Co., Ltd.) is used to binarize the read SEM image, adjust the brightness range in a manner that the grain boundary becomes clear, and identify the particles from the field of view (area). The grain size obtained by using Image-Pro Plus refers to: for the length of the line segment obtained by connecting the contour lines passing through the center of gravity obtained by the contour lines of the crystal particles, the grain size obtained by measuring and averaging with the center of gravity and a scale of 2 degrees, in the SEM photo images (3 fields of view) of each embodiment and comparative example, the average value of the grain size of all particles not involving the end of the image is set as the average grain size (number basis) in the sintered body.
[0298] "Particles not involving the image ends" refers to particles within the SEM photo image except for particles whose outlines do not completely fall within the screen (particles whose outlines are disconnected at the upper, lower, left, and right boundaries). The grain size of all particles not involving the image ends is selected in Image-Pro Plus using the option to exclude particles on all boundaries.
[0299] The average grain size of the crystal particles in the black zirconia composite sintered body of Example 3 was 2.7 μm, and the average grain size of the crystal particles in the black zirconia composite sintered body of Example 8 was 2.2 μm.
[0300] [Evaluation of processability of black zirconia composite sintered body]
[0301] For the samples of the block-shaped black zirconia composite sintered body (HIP-treated sintered body) of each embodiment and comparative example, 30 samples with metal fixtures bonded to the surface of about 15.7 mm in width and 14.5 mm in height were prepared, and processed into the crown shape of general front teeth using the CEREC system "MC-XL" (manufactured by Dentsply Sirona). It should be noted that the present invention is not particularly intended for dental use, but as a method for evaluating the degree of processability of the sintered body, the processing test was carried out using a dental processing machine and in the front tooth shape from the perspective that either the processing time or the number of processed pieces is appropriate.
[0302] The processing program used the software "inLab (registered trademark) CAMvirsion20.0.1.203841", and selected Manufacturer: IVOCLAR VIVADENT, Material name: IPS e.max CAD, Production Method: Grinding, Block size: C16. The processing tools used were Step Bur 12 and Cylinder Pointed Bur 12S.
[0303] [Processing time]
[0304] The processing time shown in Tables 1 and 2 is the time required to complete the processing of the first sample using a new processing tool under the conditions described in the above [Evaluation of Processability of Black Zirconia Composite Sintered Body]. The case where one sample could not be processed even after more than 120 minutes was marked as "×".
[0305] In addition, if an error occurs due to the load during processing and the CEREC system "MC-XL" stops processing, a new processing tool is replaced and processing is restarted. This operation is repeated until one sample is processed, and the required time is taken as the processing time.
[0306] [Number of pieces processed]
[0307] The number of samples processed shown in Tables 1 and 2 refers to the number of samples that can be processed into the crown shape of the front teeth without changing the processing tools once, using a new set of processing tools and starting the processing of the samples under the conditions described in the above [Evaluation of the processability of the black zirconia composite sintered body]. The maximum number of samples used in the test was 30, and when 30 samples were processed with one processing tool, no additional processing test was performed, and it was always set as "30 or more".
[0308] In addition, before the processing of the first sample is completed, an error occurs due to the load during processing, etc., and the MC-XL stops processing in the middle, and then replaces it with a new processing tool and restarts the processing. This operation is repeated until one sample is processed, and the reciprocal of the number of processing tools used is used as the number of processing. For example, "0.2" in Comparative Example 2 of Table 2 means that 5 processing tools are used to obtain a sample processed into the shape of a crown of a front tooth. The results are shown in Tables 1 and 2 below.
[0309]
Table 1
[0310]
[0311]
Table 2
[0312]
[0313] From the above results, it can be confirmed that the black zirconia composite sintered body of the present invention has excellent machinability despite being in the state of a sintered body. In addition, it can be confirmed that the black zirconia composite sintered body of the present invention has appropriate strength. In addition, in Examples 1 to 17, the consumption of the processing tool can be suppressed, and the number of processed bodies that can be continuously processed by one processing tool can be increased compared to the prior art.
[0314] On the other hand, in Comparative Example 1 which does not contain Nb 2 O 5 and Ta 2 O 5 , machining cannot be performed.
[0315] In Comparative Example 2 which did not contain a terminal element or ion, the processing time was not sufficiently shortened and the number of processed pieces was also very small.
[0316] In Comparative Example 3 containing a divalent metal element as a metal element not included in the terminal element, the reduction in processing time was insufficient.
[0317] In Comparative Example 4 containing a trivalent metal element as a metal element not included in the terminal element, the reduction in processing time was insufficient.
[0318] In addition, in Patent Document 4, if the addition amount of TiO2 is increased, the strength decreases in proportion to the addition amount (Figure 7 of Patent Document 4). However, in the black zirconia composite sintered body of the present invention, based on the comparison between Example 4 and Example 5, it was confirmed that when containing Nb2O5 and / or Ta2O5 as components, by also including capping elements or ions, TiO2 acts as a whole and can improve the strength of the black zirconia composite sintered body.
[0319] Industrial Applicability
[0320] The black zirconia composite sintered body of the present invention exhibits a black color that is excellent in machinability and designability.
[0321] Explanation of symbols
[0322] 1 Zirconia particles
[0323] 2 peeling ingredients
[0324] 3. Adhesive ingredients
[0325] 4. There is no grain boundary of peeling component
Claims
1. A black zirconia composite sintered body comprising ZrO2, HfO2, a stabilizer capable of inhibiting phase transformation of zirconia, and Nb2O5 and / or Ta2O5, In the total of 100 mol% of ZrO2, HfO2, the above stabilizer, Nb2O5 and Ta2O5, The total content of ZrO2 and HfO2 is 78-97.5 mol%. The content of the stabilizer is 1 to 12 mol%. The total content of Nb2O5 and Ta2O5 is 1 to 9 mol%. The black zirconia composite sintered body further includes elements or ions derived from a capping agent.
2. The black zirconium oxide composite sintered body according to claim 1, wherein: The content of the element or ion derived from the capping agent is greater than 0 mol % and less than 5.0 mol % relative to 100 mol % of the total of ZrO 2 , HfO 2 , the stabilizer, Nb 2 O 5 and Ta 2 O 5 .
3. The black zirconium oxide composite sintered body according to claim 1 or 2, wherein: Using a sample having a diameter of 15 mm and a thickness of 1.2 mm, the chroma C* calculated from a* and b* measured on a white background of the L*a*b* colorimetric system is 10 or less.
4. The black zirconium oxide composite sintered body according to claim 1 or 2, wherein: The color values obtained by measuring the color of a sample having a diameter of 15 mm and a thickness of 1.2 mm on a white background of the L*a*b* color system are L*≤60, |a*|≤3, and |b*|≤3.
5. The black zirconia composite sintered body according to any one of claims 1 to 4, wherein The aforementioned element or ion derived from the capping agent includes at least one element or ion thereof selected from Cu, Ag, Li, Na, K, Rb, Cs, Fr, At, I, Br, Cl and F.
6. The black zirconia composite sintered body according to any one of claims 1 to 5, wherein When the content of the above-mentioned stabilizer is set to A mol % and the total content of Nb2O5 and Ta2O5 is set to B mol %, A / B is greater than or equal to 0.9 and less than or equal to 3.
7. The black zirconia composite sintered body according to any one of claims 1 to 6, wherein The aforementioned stabilizer includes Y2O3 and / or CeO2.
8. The black zirconia composite sintered body according to any one of claims 1 to 7, wherein It also contains a zirconium oxide reinforcing agent, and the content of the above-mentioned zirconium oxide reinforcing agent is greater than 0 mass% and is 5.0 mass% or less relative to 100 mass% of the total of ZrO2, HfO2, the above-mentioned stabilizer, Nb2O5 and Ta2O5.
9. The black zirconium oxide composite sintered body according to claim 8, wherein: The aforementioned zirconium oxide reinforcing agent includes TiO2 and / or Al2O3.
10. The black zirconia composite sintered body according to claim 9, wherein: The zirconium oxide reinforcing agent contains TiO 2 , and the content of TiO 2 is 0.6 to 3.7% by mass.
11. The method for producing a black zirconia composite sintered body according to any one of claims 1 to 10, comprising: A step of producing a formed body using a raw material composition, wherein the raw material composition comprises ZrO2, HfO2, a stabilizer capable of suppressing phase transformation of zirconium oxide, and Nb2O5 and / or Ta2O5, In the total of 100 mol% of ZrO2, HfO2, the above stabilizer, Nb2O5 and Ta2O5, The total content of ZrO2 and HfO2 is 78-97.5 mol%. The content of the stabilizer is 1 to 12 mol%. The total content of Nb2O5 and Ta2O5 is 1 to 9 mol%. The raw material composition further comprises a capping agent; and A step of sintering the molded body.
12. The method for producing a black zirconium oxide composite sintered body according to claim 11, wherein: The step of sintering the molded body includes a step of performing reduction sintering.
13. The method for producing a black zirconium oxide composite sintered body according to claim 11 or 12, wherein: The terminal blocking agent contained in the raw material composition is a compound capable of forming a monovalent ion. The method for producing a zirconium oxide composite sintered body further includes a step of wet-mixing the respective raw materials of the raw material composition in a solvent containing water to obtain the raw material composition.
14. The method for producing a black zirconia composite sintered body according to any one of claims 11 to 13, wherein: In the raw material composition, the stabilizer includes a stabilizer that is insoluble in ZrO 2 and HfO 2 .
Citation Information
Patent Citations
Black-colored free-cutting ceramics, its manufacturing method and use thereof
JP2001354480A
Black zirconia sintered compact, raw material powder for the same, and method of manufacturing them
JP2006342036A
Machinable zirconia and method for producing the same
JP2015127294A
Black zirconia sintered body and use therefor
JP2017077976A
Manufacture of zirconia black sintered body
JP1986117156A